The level of achievement of total quality management standards from the point of view of the teaching staff of the faculty of physical education at Kerbala University - Aied Kareem Al-Kenani; Aziz Kareem Wanas (University of Science and Technology, Yemen, 2013)
Abstract                                                                                                 The aim of the study was to identify the level of achievement of total quality management standards from the point of view of the teaching staff of the faculty of physical education at Kerbala University. The sample of the study included 34 teaching staff and data analysis revealed that in total, the level achievement of total quality is poorly achieved. With regard to the categories of the questionnaire, the first and the fourth were very poorly achieved while the second is poorly achieved and the third is highly achieved. The researchers recommend that the faculty should work on capacity building and developing the teaching staff performance, and making similar studies on other faculties of the university  of Kerbala